2023
DOI: 10.3390/molecules28031482
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabelling of Polyclonally Expanded Human Regulatory T Cells (Treg) with 89Zr-oxine for Medium-Term In Vivo Cell Tracking

Abstract: Regulatory T cells (Tregs) are a promising candidate cell therapy to treat autoimmune diseases and aid the longevity of transplanted solid organs. Despite increasing numbers of clinical trials using human Treg therapy, important questions pertaining to their in vivo fate, distribution, and function remain unanswered. Treg accumulation in relevant tissues was found to be crucial for Treg therapy efficacy, but existing blood-borne biomarkers are unlikely to accurately reflect the tissue state. Non-invasive Treg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…57 Unfortunately, nuclear imaging will not fulfill our clinical need to track delicate NK cells in pediatric populations and due to potential cytotoxic effects of 89 Zr on cell activity even at low doses per cell. 30 As we demonstrate in this work, MPI to addresses the limitations of current cellular imaging techniques. MPI specifically identifies the location of iron-labeled cells and produces a specific (hotspot) image [31][32][33][34][35][36][37][38] , similar to images obtained by 19 F MRI and nuclear imaging.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…57 Unfortunately, nuclear imaging will not fulfill our clinical need to track delicate NK cells in pediatric populations and due to potential cytotoxic effects of 89 Zr on cell activity even at low doses per cell. 30 As we demonstrate in this work, MPI to addresses the limitations of current cellular imaging techniques. MPI specifically identifies the location of iron-labeled cells and produces a specific (hotspot) image [31][32][33][34][35][36][37][38] , similar to images obtained by 19 F MRI and nuclear imaging.…”
Section: Discussionmentioning
confidence: 95%
“…57 Unfortunately, nuclear imaging will not fulfill our clinical need to track delicate NK cells in pediatric populations and due to potential cytotoxic effects of 89 Zr on cell activity even at low doses per cell. 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Jacob et al, polyclonal expanded human Tregs were successfully tracked and monitored using radiolabeled 89 Zr-oxine in immunodeficient mice for three days. The results showed that this radiolabeling did not affect the viability of Tregs or their suppressive activities [ 147 ]. Another study involved radiolabeling of CD4 + T cells with Tc-99 m (Technetium-99 m pertechnetate), enabling Treg biodistribution assessment within a day [ 149 , 154 ].…”
Section: Biomaterials To Facilitate Enhancement In Treg Functionsmentioning
confidence: 99%